Moral and Psychological Stability of Police Officers in the System of Their Professionally Important Qualities - I. V. Klymenko (Law and Safety)
Issues related to the assessment of the professionalism of police officers are inevitably intertwined with the increasing role of the moral foundations of their activities. The implementation of generally accepted rules of conduct, which are formed in the legal consciousness of the individual, reflects the level of his moral and legal thinking. In our context, the peculiarity of morality is that it is manifested not only in the content of the police, but also in the form of its implementation, playing the role of the most important factor in assessing the work of the police by society.